Analisis Penerimaan Learning Management System Menggunakan Model UTAUT 2 Pada Universitas Tadulako - Putu Nathania Ardiyani; Yani Rahardja; Johan J.C Tambotoh (JATISI (Jurnal Teknik Informatika dan Sistem Informasi), 2023)
Learning Management System (LMS) is an e-learning or online learning media provided by Tadulako University to facilitate interaction between students and lecturers. The purpose of this study was to determine the opinion of students on the acceptance of LMS provided by the University. This study uses the UTAUT 2 model to examine the factors of the LMS (performance expectations, business expectations, social influence, facility conditions, hedonic motivation, habits and behavioral intentions to use). This research was conducted using quantitative research methods. Data analysis using SEM-PLS technique with the help of SmartPLS version 3.29. Validity testing is done by looking at the value on the outer loading, reliability testing is carried out to assess the alpha, composite and AVE methods. This research was conducted by distributing online questionnaires to active students at Tadulako University. The results obtained from this study for testing the validity and reliability were declared valid on each variable because it had an AVE value of more than 0.5, an alpha of more than 0.6 and a composite of more than 0.7. For the results of hypothesis testing in this study 12 hypotheses, 7 rejected hypotheses and 5 accepted hypotheses.